Acne Severity Fluctuations Across Menstrual Phases in Adolescents - Shinta Galuh Permata; Sitti Hajjar; Hedya Nadhrati Surura (Fakultas Kedokteran Universitas Malikussaleh, 2026)
Acne vulgaris is a chronic inflammatory disorder of the pilosebaceous unit, commonly affecting adolescents and influenced by hormonal fluctuations, particularly in females with active menstrual cycles. This repeated-measures observational analytic study aimed to analyze differences in acne severity between premenstrual and postmenstrual phases among adolescent girls. A total of 69 female students aged 15-18 years were selected through purposive sampling from a senior high school in Aceh Besar, Indonesia. Data were obtained through structured interviews and facial photography during two menstrual phases. Acne severity was assessed by a board-certified dermatologist based on the Indonesian Dermatology and Venereology Clinical Practice Guidelines. Statistical analysis using the marginal homogeneity test demonstrated a significant difference in acne severity between menstrual phases (p < 0.001). Clinical improvement after menstruation was observed in 24 participants (34.8%; 95% CI: 23.7-47.2%). During the premenstrual phase, most participants had moderate acne (61%), whereas mild acne predominated in the postmenstrual phase (55%). In conclusion, acne severity was more frequently observed during the premenstrual phase and appeared to be associated with menstrual cycle-related hormonal fluctuations. These findings support the importance of menstrual cycle-based clinical evaluation in adolescent females with acne vulgaris.